2005
DOI: 10.1007/11555261_104
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Tracking Reveals the Personal Styles for Search Result Evaluation

Abstract: Abstract. We used eye-tracking to study 28 users when they evaluated result lists produced by web search engines. Based on their different evaluation styles, the users were divided into economic and exhaustive evaluators. Economic evaluators made their decision about the next action (e.g., query re-formulation, following a link) faster and based on less information than exhaustive evaluators. The economic evaluation style was especially beneficial when most of the results in the result page were relevant. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 7 publications
8
76
0
1
Order By: Relevance
“…Aula et al [3] identified two general patterns that people used in examining search results: exhaustive evaluators (54% of the participants who looked at more than half of the visible results for more than half the tasks) and economic evaluators (46% of the participants). Dumais et al [12] performed a similar analysis of search behavior using more complex result pages that included both organic results and advertisements.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Aula et al [3] identified two general patterns that people used in examining search results: exhaustive evaluators (54% of the participants who looked at more than half of the visible results for more than half the tasks) and economic evaluators (46% of the participants). Dumais et al [12] performed a similar analysis of search behavior using more complex result pages that included both organic results and advertisements.…”
Section: Related Workmentioning
confidence: 99%
“…However these studies are typically conducted in laboratories using a small number of participants with assigned tasks (e.g., [9][15]), with summaries of gaze behavior aggregated across participants and tasks. Some studies examined individual and task differences in gaze patterns, and found individual differences in the strategies with which users inspect results [12], and different clusters of users who exhibit similar result examination behaviors [3] [12]. Others found that the type of search task (informational vs. navigational) influenced task completion time and time spent reviewing documents [9] [27].…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the user behavior in the Smucker and Jethani study is representative of actual result list processing behavior given the similarity between the study's observed behavior and that reported by other researchers (cf. strategies in Aula [1] and Dumais et al [9], probabilities of clicking on summaries in Yilmaz et al [31]). …”
Section: Calibration Of Model Componentsmentioning
confidence: 99%
“…This is the case, for instance, when studying gaze behaviour on web pages that are composed of horizontally or vertically arranged blocks of information. Another natural application is studies of menu usage [2,3].…”
Section: Static Visualization Of Temporal Gaze Datamentioning
confidence: 99%
“…Time plot visualizations make it possible to visually observe differences in the gaze behaviour of different users. We have used the technique for analyzing how users perceive search result listings (see [2] for more examples).…”
Section: Static Visualization Of Temporal Gaze Datamentioning
confidence: 99%